ANALISIS SASARAN KERJA PEGAWAI DI KANTOR DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PALU - Nirwana, Dewi Sri; Mustainah, Mustainah; Amir, Andi Mascura (Katalogis, 2020)
The results of the study show that Taking into account the analysis of employee performance will be illustrated where the strengths and weaknesses of employees in completing the work that has been charged. Find out where the location or cause of the error occurred so that employees know exactly what is being faced. Why has not finished the work entrusted to him and how the solution to the problem. So that this can be a motivation for employees to solve problems and can rise to high performance in the future. So that the effectiveness of the Employee Work Target can be better than expected.